Molecular Localization of Human Papilloma Viral 16/18 DNA in Adenoctomized Tissues from a group of Iraqi Patients (Medico Legal Update, 2020)
Background: Low- and high- oncogenic risk human papilloma viral infections have been related to thegenesis of a variety of human benign and malignant tumors in the oral cavity and nasopharyngeal tissues.High- risk types of human papilloma virus are now well established as major etiologic factors of headand neck cancers, including tonsillar carcinomas. Objective: The current prospective case- control studyaimed to unravel the frequency of HPV genotype 16/18 DNA detection rates in the adenoctomized tissuesfrom patients with nasopharyngeal tonsillar adenoid hypertrophy. Materials and Method: A sixty (60)nasal as well as nasopharyngeal adenotonsillar tissues obtained from patients with adenoid hypertrophy viaadenoctomies were enrolled. Forty (40) adenotonsillar tissues were from patients with adenoid hypertrophy,and (20) normal nasal tissue specimens were obtained from pediatric patients following trimming operationsof inferior nasal turbinates’ with unremarkable pathological changes (as an apparently healthy controlgroup). A recent version of chromogenic in situ hybridization (CISH) method for HPV detection wereperformed by using specified DNA probes for DNA of high- risk HPV 16/18 genotypes. Results: Amongnasopharyngeal adenotonsillar tissues group, 15 out of 40 have revealed positive CISH signals for DNA ofHPV 16 / 18 genotype, constituting 35% of the total screened adenoid hypertrophied tissues. No positive–CISH reactions were detected in the control nasal tissues. Statistically, the results obtained in this studyshowed significant difference when compared to the control tissues group. Conclusions: The significant rateof such high- oncogenic HPV genotypes detection in those nasopharyngeal adenotonsillar tissues criticizessearching its further importance, as HPV 16/18 genotypes are critically correlated to many pre- neoplasticas well as malignant lesions.